Bridging The Skills Gap: Market-Relevant Skill Development Programmes in Nepal’s Health Sector - Acharya, Devaraj; Devkota, Bhimsen; Adhikari, Eka Raj; van Teijlingen, Edwin Roland; Thapa, Krishna Bahadur (Journal of Technical Education and Training, 2026)
Council for Technical Education and Vocational Training is an autonomous body that produces basic to mid-level technical human resources and is responsible for overseeing Technical and Vocational Education and Training in Nepal. This study aims to explore the potential new courses for PCL/Diploma level in the health sector. A qualitative research design was employed to identify new areas. Participants were selected based on their experiences in the health sector in both Nepal and abroad. A total of 25 in-depth interviews, and two interactive meeting events were conducted, and thematically analyzed. The health courses identified for PCL/Diploma level within the health sector were: nursing, general medicine, Ayurveda, food science, and water, sanitation and hygiene, physiotherapy and rehabilitation, laboratory, health education and health promotion, medical records and data, health and social care, and radiotherapy. Courses identified as being in higher demand in Nepal and were: renal dialysis, radiotherapy, prosthetics and orthotics, audiology and speech language therapy, transfusion and blood banking, medical transcript, geriatric care, school nurse, palliative care, telemedicine and telehealth, cancer care, OT/anesthesia assistant, IVF and reproductive medicine, Panchkarma, herbs and shrubs, WASH and hospital hygienist, occupational therapy, health and social care, and data and medical records.  All these courses, however appealing and demanding in the market, need to be approved for registration and licensing from the relevant professional councils in Nepal. Before commencing the new programmes/courses, they should be assessed and interacted with the stakeholders, regulatory bodies, and even the general public.